2012
DOI: 10.1371/journal.pone.0044993
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Study of Spatially Heterogeneous Emphysema Progression in Current Smokers with Chronic Obstructive Pulmonary Disease

Abstract: BackgroundCigarette smoke is the main risk factor for emphysema, which is a key pathology in chronic obstructive pulmonary disease (COPD). Low attenuation areas (LAA) in computed tomography (CT) images reflect emphysema, and the cumulative size distribution of LAA clusters follows a power law characterized by the exponent D. This property of LAA clusters can be explained by model simulation, where mechanical force breaks alveolar walls causing local heterogeneous lung tissue destruction. However, a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 32 publications
(75 reference statements)
4
33
2
Order By: Relevance
“…Consistent with previous studies (Matsuoka et al ., ; Tanabe et al ., ), the current study demonstrated that pulmonary emphysema in patients with COPD progressed during the follow‐up period. However, a gradual time‐dependent change in small pulmonary vascular CSA was not observed for the %CSA <5 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent with previous studies (Matsuoka et al ., ; Tanabe et al ., ), the current study demonstrated that pulmonary emphysema in patients with COPD progressed during the follow‐up period. However, a gradual time‐dependent change in small pulmonary vascular CSA was not observed for the %CSA <5 .…”
Section: Discussionsupporting
confidence: 59%
“…Previous longitudinal studies have shown that the extent of emphysema gradually increases over time (Matsuoka et al ., ; Tanabe et al ., ). However, to the best of our knowledge, longitudinal changes of small pulmonary vessels in patients with COPD have not been evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…The outcome of these procedures was then compared to the CT image of the subject taken at a later time. This modeling approach not only confirmed the original force-based coalescence of LAA clusters, but also revealed that the model works only when small LAA clusters merge into nearby larger clusters providing evidence that diseased areas tend to grow possibly due to larger than average stresses around the perimeter of existing already damaged regions (34). …”
Section: Modeling Alveolar Structure In 2dsupporting
confidence: 52%
“…In COPD, it has been demonstrated that patients with higher quantities of emphysema on CT have an increased rate of decline of FEV1 [34,50]. CT emphysema progression is also associated with frequent exacerbations [64] and current smoking status [65]. The largest longitudinal study to date assessed CT scans from the ECLIPSE cohort [66] where they found lung density and low attenuation areas progressed on an annual basis.…”
Section: Emphysemamentioning
confidence: 99%